2021
DOI: 10.1155/2021/9987200
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual Reality Technology Combined with Comprehensive Pulmonary Rehabilitation on Patients with Stable Chronic Obstructive Pulmonary Disease

Abstract: With the popularization of medical knowledge and the development of medical technology, people pay more and more attention to COPD. This paper mainly studies the effect of virtual reality technology combined with comprehensive lung rehabilitation on patients with stable chronic obstructive pulmonary disease. 60 patients with stable chronic obstructive pulmonary disease were selected to collect their general information, such as name, gender, and age. They were divided into the experimental group and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
(11 reference statements)
0
19
0
1
Order By: Relevance
“…All included studies (Table 2) had added a VR component to usual PR, which was the main rehabilitation strategy for COPD patients. The technological equipment varied across the studies from the Microsoft Xbox Kinect [27,28] and Nintendo Wii Fit [24,25] to head-mounted displays [15,26]. The Xbox 360 console was used along with the Kinect motion sensor in order to detect and follow the participants' movements.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…All included studies (Table 2) had added a VR component to usual PR, which was the main rehabilitation strategy for COPD patients. The technological equipment varied across the studies from the Microsoft Xbox Kinect [27,28] and Nintendo Wii Fit [24,25] to head-mounted displays [15,26]. The Xbox 360 console was used along with the Kinect motion sensor in order to detect and follow the participants' movements.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Dyspnoea will be primarily assessed using the Medical Research Council scale and the Borg scale 24 25. Quality of life will be evaluated through various instruments, including the capacity index (BODE), St. George’s Respiratory Questionnaire, COPD Assessment Test, or other validated tools 26–28. Physical function in patients with COPD will be assessed using the Senior Fitness Test (formerly referred to as the Functional Fitness Test or Fullerton test) 29.…”
Section: Methods and Analysismentioning
confidence: 99%
“…FEV1% predicted. A total of 4 studies [27,32,33,37] reported FEV1 as an outcome. Due to the obvious heterogeneity (I 2 = 64%, P = .0039), a random-effect model was adopted.…”
Section: Meta-analysisamentioning
confidence: 99%
“…Moreover, 5 articles were excluded due to did not meet the inclusion criteria. Finally, a total of 11 studies [26,27,[31][32][33][34][35][36][37][38][39] were included in the meta-analysis (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation